THE EFFECTIVENESS OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TO TEACH WRITING VIEWED FROM STUDENTS’ CREATIVITY - aseptiana parmawati (STKIP Siliwangi, 2015)
The research was conducted at finding out whether (1) CIRC is more effective than Direct Method; (2) the eighth grade students of SMP N 2 Cepu Central Java who have high creativity have better writing skill than those having low creativity; and (3) there is interaction between teaching methods and students’ creativity to teach writing. This research was done in SMP N 2 Cepu Central Java. The subject of the research is the eighth grade students in the academic year of 2012 – 2013. The method which was applied in this research was experimental Study. The samples were taken by using cluster random sampling technique. The class 8F was used as the experimental class and class 8E as the control class. Each of the classes consisted of 30 students. The data were obtained from students’ score of creativity test and score of writing test. To analyze the data, researcher used descriptive analysis, ANOVA, and Tukey test.The result of the research shows that: (1) CIRC is more effective than Direct Method in teaching writing for eighth grade students of SMP N 2 Cepu Central Java; (2) students who have high creativity have better writing skill than students who have low creativity; (3) there is an interaction between teaching methods and students’ creativity in teaching writing at the eighth grade students of SMP N 2 Cepu Central Java. Based on the findings, it can be concluded that CIRC is an effective method to teach writing viewed from students’ creativity at the eighth grade students of SMPN 2 Cepu Central Java. Recommendations are addressed to English teachers and future researchers. English teacher should consider utilizing CIRC due to the benefits of the method. For future researchers, it is suggested to conduct more sophisticated research on the same topic. Keywords: CIRC, Direct Method, Creativity